“Apruebo Este Mensaje:” How the Language of Political Communication Affects the Political Attitudes of Linguistically Diverse Latino Voters. - Ramirez, Lorenza L. (Tufts Archival Research Center, 2018)
Every election cycle, political campaigns on both sides of the aisle spend millions of dollars on Spanish-language advertising in an effort to appeal to Latino voters. Yet there is no consensus among scholars that using a particular language positively--or negatively--impacts the political attitudes of linguistically diverse Latino voters. Furthermore, in the existing academic field of Latino politics, the framework of analysis has been largely binary: researchers have distinguished only between “Spanish-dominants” and “English-dominants,” with no acknowledgement for the political attitudes and behavior of bilingual Latinos, who make up 36% of the Latino population in the United States today. This study fills this gap by studying how the language of political communication affects the favorability of a non-Latino candidate among bilingual versus English-dominant Latino voters. To do so, I utilized a qualitative methodology and conducted a series of twelve focus groups with Latino-identifying students at Tufts University. In each focus group, participants either viewed a Spanish or English-language advertisement, and were asked to rate their favorability of the candidate and his commitment to the Latino community, as well as respond to a series of discussion questions pertaining to the effect of the language of political communication. The findings from these focus group survey questions and discussions confirmed that bilingual Latinos and English-dominants embrace distinct political attitudes about Spanish-language political communication and partisanship. Furthermore, this research demonstrates that the role of Spanish in Latino identity is changing, and provides practical recommendations for political campaigns to improve their strategies to effectively engage with bilingual and English-dominant Latino voters.